Pilot randomized trial of high- and low-frequency repetitive transcranial magnetic stimulation in post-stroke depression with EEG monitoring - Su, Xiaolin; Zhu, Lin; Shi, Xue; Pei, Zian; Hordacre, Brenton; Yan, Nan; Guo, Yi; Dang, Ge (Frontiers in Neurology, 2025)
BackgroundPost-stroke depression (PSD) is a prevalent complication that adversely affects recovery following stroke. Repetitive transcranial magnetic stimulation (rTMS) has garnered attention as a potential therapeutic intervention for PSD. This pilot double-blind randomized trial aimed to assess the feasibility and preliminary effects of high- and low-frequency rTMS in PSD, while exploring potential neural mechanisms using electroencephalography.MethodsChronic stroke survivors diagnosed with PSD were randomly allocated to receive either high-frequency rTMS targeting the left dorsolateral prefrontal cortex or low-frequency rTMS targeting the right dorsolateral prefrontal cortex for 20 sessions. Hamilton Depression Rating Scale were assessed, and resting-state electroencephalography were recorded at baseline, mid-treatment, and post-treatment.ResultsBoth high- and low-frequency rTMS were well tolerated and reduced depressive symptoms at mid- and post-treatment. Electroencephalography analysis did not reveal divergent neural signatures associated with the two protocols. However, altered connectivity linking posterior divisions of the middle frontal gyrus and specific regions in the theta- and beta-band frequencies were associated with the improvement in Hamilton Depression Rating Scale scores.ConclusionThis pilot study provides preliminary evidence that rTMS is feasible for managing PSD across both high- and low-frequency protocols. EEG analyses suggest potential neurobiological mechanisms, which may inform future research on treatment optimization.Clinical trial registrationchictr.org.cn, ChiCTR1900021168.